The Improvement of National Awakening Spirit Learning in Social Personal Using Cooperative Learning Model - Hasan Jamani (JP2D (Jurnal Penelitian Pendidikan Dasar) UNTAN, 2022)
The research aims to increase knowledge and understanding of students duringcitizenship education earning about the spirit of national awakening spirit in personal social through cooperative learning model. A method used in this research was Classroom Action Research (CAR). The researcher used the method with the research approach given o solve the problem in this case providing a solution with quantitative descriptive. It is a way of determining how to obtain data on these variables. In research activities, researchers follow an appropriate procedure by obtaining data. A totaling 32 students in he eighth grade of A at SMPN 4 Sungai Raya participated in this study. Based on theresults of the pre-cycle, among 32 students only 11 students passed the test with a percentage of 34%. In cycle 1, 27 students passed with a percentage of 84% and continued o cycle II with improved planning and implementation. In cycle II, 32 students passed with a 100% percentage. Cooperative learning model can help students to understand about certain topics because there are smaller and more effective groupings.